2014
DOI: 10.1590/s1982-88372014000100010
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Evaluation of Tungsten Oxide Nanoparticles in Cultured Rat Liver Cells for Its Safe Applications in Nanotechnology

Abstract: Tungsten (VI) oxide (WO 3 ) nanoparticles (NPs) are used for many industrial purposes in everyday life. However, their effects on human health have not been sufficiently evaluated. Therefore, the present study was designed to investigate the toxicity potentials of various concentrations (0 to 1000 ppm) of WO 3 NPs (<100 nm particle size) in cultured primary rat hepatocytes. The results of cell viability assay showed that the higher concentrations of dispersed WO 3 NPs (300, 500 and 1000 ppm) caused significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…In contrast, plasma and laser ITER-like W-NPs showed significant cytotoxicity on BEAS-2B cultures, they resulted genotoxic by significantly enhancing the MN frequency and by inducing DNA strand breaks. In agreement with previous studies [25,26], we equally observed oxidative stress that might have triggered DNA damage. Nevertheless, the differences between our results and those of Turkez and coauthors [25,26] might be due to the fact that only a fraction of our ITER-like W-NPs was oxidized.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In contrast, plasma and laser ITER-like W-NPs showed significant cytotoxicity on BEAS-2B cultures, they resulted genotoxic by significantly enhancing the MN frequency and by inducing DNA strand breaks. In agreement with previous studies [25,26], we equally observed oxidative stress that might have triggered DNA damage. Nevertheless, the differences between our results and those of Turkez and coauthors [25,26] might be due to the fact that only a fraction of our ITER-like W-NPs was oxidized.…”
Section: Discussionsupporting
confidence: 93%
“…Since the presence of WO 2 and WO 3 we detected during powders characterization is not negligible [24], oxidation should also be considered when analyzing plasma and laser ITER-like W-NPs toxicity. Ex vivo bone cells and hepatocytes of 8 weeks old male Sprague-Dawley rats were used to investigate the cytotoxicity, the genotoxicity, and the mutagenic potential of WO 3 NPs [25,26]. Upon 30 days of intraperitoneal injections of WO 3 NPs at the dose of 25–50–100 mg/kg b.w., bone cells were collected from tibia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations